Eyeglass glare and reflection removal - Sim, Kim Soon (Nanyang Technological University, 2021)
The purpose of inpainting is to restore the missing or damaged regions of an image using the information from the surrounding pixels. The estimation of the pixel value is done through making isophote lines continuous in the image. Compared to traditional methods, the need to introduce the origin of the information is removed because of inpainting. This allows multiple regions of missing information to be filled in concurrently.